Breastfeeding With Recurrent Acute Respiratory Tract Infections (Ari) In Toddler At Gotong Royong Hospital Surabaya - Melati, Irene; Susan, Susan; Nawang, Galuh (JOURNAL OF WIDYA MEDIKA JUNIOR, 2019)
Introduction: Acute Respiratory Tract Infection (ARI) is a common illness in children under five years old. The incidence of ARI in developing countries is ten times more than in developed countries. There are many risk factors for ARI, such as breastfeeding. Aim: The purpose of this study is to determine the relationship between exclusive breastfeeding with the occurrence of recurrent ARI in children under five. Method: This research uses an analytic research design with an observational study type and a cross-sectional study method. The numbers of samples in this study were 203 samples and tested using the chi-square test. The data of 203 samples in this study were obtained from primary data with structured interviews regarding exclusive breastfeeding and secondary data by looking at the patient's medical records regarding the occurrence of recurrent ARI. From 203 selected samples, 47.3% are exclusively breastfed, and 52.7% are not exclusive breastfeeding. Recurrent ARI events were calculated over the past year with the criteria for ARI greater than or equal to six times. Result: The results of this study are that 53.7% of samples do not have recurrent ARI, and 46.3% of samples have recurrent ARI. The results of this study show a p-value of 0.00, which means there is a significant relationship of exclusive breastfeeding with the occurrence of recurrent ARI in children under five years old. Conclusion: The incidence of Recurrent ARI in children under five years old with exclusive breastfeeding history is lower than children under five years old without exclusive breastfeeding history.